ANALISIS DIKSI DALAM OPINI PADA KORAN SERAMBI EDISI AGUSTUS 2024 - s, Nofiana; Rahmi, Hayatun; kamisna, Mina (Jurnal Sosial Humaniora Sigli, 2024)
This study aims to analyze the selection of diction in opinion articles published in the August edition of Porch Newspaper. Diction, as an important element in written communication, plays a crucial role in shaping perceptions and influences on readers. This research uses a qualitative approach with a text analysis method to identify and categorize the types of diction used in opinion articles. The main focus of the research is to reveal how word choice can create a certain tone, strengthen arguments and influence public opinion on the issues discussed. The results of the analysis are expected to provide insights into word choice patterns and how they can influence readers' interpretations. This research is also expected to provide recommendations for improving the quality of language use in the mass media, especially in writing more objective and effective opinions. The formulation of the problem is how the selection of diction in opinion articles in the August edition of the foyer newspaper can affect the meaning and message conveyed? the conclusion of this study is that student activeness has increased after doing the assignments that have been distributed. The suggestion of this study is that student activeness has increased after doing the assignments that have been distributed. but also can influence readers positively, and not confuse readers.Keywords: Diction, Opinion, Serambi Newspaper,